Correlation studies between structural and ionic transport properties of lithium-ion gel polymer electrolytes based on guar gum - Aynharn, S.; Ahmad Faizrin, Ahmad Fuzlin; Ahmad Salihin, Samsudin (Springer Berlin Heidelberg, 2025)
Novel gel polymer electrolytes (GPEs) based on guar gum and lithium bis(oxalate)borate (LiBOB) were developed via the dissolution method. Structural and ionic conductivity properties were investigated using Fourier-transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and electrochemical impedance spectroscopy (EIS). FTIR analysis revealed significant interactions between guar gum and LiBOB. DSC results indicated a decrease in both the glass transition temperature (Tg) and crystallization temperature (Tc) with increasing LiBOB content, reflecting enhanced amorphous phase formation. An optimum ionic conductivity of 7.89 × 10−4 S cm−1 at room temperature was achieved with 6 wt. % LiBOB. The temperature dependence of conductivity followed Arrhenius behavior, suggesting thermally activated ion transport. FTIR deconvolution established a correlation between the number density, mobility, and diffusion coefficient of mobile ions with ionic conductivity. These findings demonstrate the potential of guar gum–based GPEs for lithium-ion battery applications.